Financing of public-private partnerships: post-crisis reality and perspectives - Літвінова, Наталя Сергіївна (Eastern-European Journal of Enterprise Technologies, 2013)
In conditions of a usual state budget deficit, the public-private partnership has been acting as an inevitable alternative to finance infrastructure projects in the world. Despite the considerable number of publications on the topic of PPP, they still have not fully covered features and prospects of raising capital, especially for the conditions of modern Ukraine. Based on the accumulated world experience, the article considers the structure and key elements of the system of financing of PPP, and analyzes the main trends and priorities from the perspective of involved sources and capital instruments. In addition, as part of this article we have evaluated a number of legal and financial possibilities of PPP projects implementation in Ukraine. Therefore, the article indicates the need to modernize the domestic capital market and to overcome a number of financial and legal barriers